The status of the Sunda Coucal Ceiitropus nigrorufus Cuvier. - Andrew, Paul (KUKILA, 1990)
A historical review is presented on the taxonomic and distributional status of the Sunda Coucal Centropus nigrorufus. It is concluded that this species is endemic to Java, and that it does not occur on Sumatra as has been suggested. Its distribution In Java and habitat requirements are discussed.